The Influence of Playing on the Movement of Students with SLB Cahaya Mustahil Ngoro - Mecca Puspitaningsari (Universitas Majalengka, 2023)
Physical education is both an educational process through physical activity and an educational process that aims to improve physical abilities. Children with special needs (ABK) are children who have their own characteristics or uniqueness that make them different from normal children in general. Impairment is a term used to refer to children who have intellectual abilities that are below average. The purpose of this study is to see how playing affects the steps of students with mild mental retardation at SLB Ngoro.This study used the single-subject research (SSR) experimental research method, or so-called single-subject research. The sample in this study amounted to 1 person because they used single-subject research (SSR). The design used in this study is A-B-A. With 8 meetings for baseline phase A1, intervention, and baseline phase A2. Based on the results of calculations from the Single Subject Research (SSR) method, there is a significant influence between play variables and step motion variables on mild mental retardation students in SLB Ngoro, as evidenced by the percentage of stability in the baseline phase A1 (100%), intervention phase B (25%), and baseline phase A2 (100%) with an improved, albeit very small change in levels. At the overlap percentage, there is no data that overlaps, namely 0%, and it is said to be good because the smaller the overlap percentage, the better.